Legal Reconstruction of Empirical Juridical Analysis of Unilated Determination of Defense (Study of Pontianak District Court Decision Number 51/Pdt.G/2021/PN Ptk) - Erby, Efriza; Prastyanti, Rina Arum; Muftiyanto, R. Taufiq Nur (Lembaga Penelitian dan Pendidikan (LPP) Mandala, 2024)
Decision case number 51/Pdt.G/2021/Pn Ptk contains a legal problem, namely the unilateral determination of default and the legal consequences (the application for the sale of collateral was also carried out unilaterally). This research basically aims to find out the legality of unilateral determination of default in positive law in Indonesia and the legal construction of Pontianak State Decision No. 51/Pdt.G/2021/Pn Ptk in terms of the theory of legal certainty. This research has a normative juridical character, with a statutory approach and a case approach. Legal materials were obtained from primary legal sources (legislation and decisions) as well as secondary legal materials, namely library sources such as books and journals. The results of this research: The legality of unilateral determination of default in positive law in Indonesia refers to the Supreme Court (MA) Jurisprudence No. 186 K/Sip/1959 and based on the jurisprudence of the Republic of Indonesia Supreme Court Decision No. 852 /K/Sip/1972, in Indonesian law, it is not legal/legitimate/legitimate to carry out unilateral acts of default without a prior summons. The legal construction of the Pontianak District Decision No. 51/pdt.g/2021/pn PTK is viewed from the theory of legal certainty, namely that the judge must grant petitum number 3